Masjid Al-Musannif: Lambang Keberagaman di Kota Medan - Fitri, Mita Saskia; Siregar, Yusra Dewi; Abidin, Syahrul (Mahesa Research Center (PT. Mahesa Global Publishing), 2021)
This article discusses the architecture of the Al-Musannif Mosque which is located in the Cemara Asri complex, Medan. Al-Musannif Mosque is one of the most famous mosques in Medan City. This study uses a qualitative research method with a descriptive approach. Al-Musannif Mosque is a mosque founded by one of the well-known businessmen in the city of Medan named H. Anif Shah. This mosque was founded after H. Anif Shah experienced a spiritual incident during the pilgrimage. This mosque comes with a domed architectural design, which combines various cultures in its architecture, such as: Malay, Arabic, and European. This mosque has a large courtyard, and is often used as a place to carry out religious and social activities. Until now, the Al-Musannif Mosque is one of the mosques that is often visited by residents of the city of Medan.